Etnobotani Tumbuhan Ciplukan (Physalis angulata L.) Di Suku Dayak Seruyan Desa Telaga Pulang Kabupaten Seruyan, Kalimantan Tengah - Ridha Nirmalasari; Vira Andini; Ayatusa’adah Ayatusa’adah (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2022)
The use of the Ciplukan plant as a traditional medicine for diabetes mellitus diseases has been known for a long time by people of Dayak Seruyan tribe. This study aims to describe the ethnobotany study of the Ciplukan plant; phytochemical content and the usage techniques by people of Dayak Seruyan tribe, the village of Telaga Pulang, Seruyan regency, Central Kalimantan. This type of research is descriptive-exploratory with the approach of PEA (Participatory Ethnobotanical Appraisal) with data collection technique by interview and observation. The results showed that phytochemical content of Ciplukan plant are saponins, flavonoids, polyphenols and fisalins which this content affects the ß cells of the pancreatic insulin. People of Dayak Seruyan tribe using Ciplukan’s root as a medicine of diabetes mellitus diseases. The herb technique is by boiling it until the color of the Ciplukan root’s water is slightly reddish. The Ciplukan’s root can be directly taken in nature with the terms by placing offerings or Pekaras (rice, salt, and spike) that wrapped in a cloth or plastic instead of the root taken with say permission to take the roots from that plant. The boiled water of the Ciplukan’s root that feels very bitter by people is trusted as a medicine for diabetes mellitus diseases. People can develop the use of other medicinal plants with sustainable as a regional inventory and develop local knowledge about various kinds of traditional medicinal plants (herbals) to preserve various kinds of medicinal plants.